NDORO HABIB (BERKUASA) DI TANAH JAWA: STRATEGI MELANGGENGKAN STATUS QUO DI KOTA PEGON - Afad (Al'Adalah, 2017)
Marginality is often interpreted as a group that is always marginalized. In practice they could be the dominant actors in society. They do some tactics to maintain their comfortable position. However, marginalized people re-main marginal, they lose in social and political contestation. This research uses ethnographic methods. Researchers go directly to the research community. Researchers observe participation, in-depth interviews and record and document the things he sees, feels, hears , and smell. The results of this stu-dy indicate that the figure of Habib who is a charismatic actor. But some of the people did not like it and did the resistance. Habib's presence is referred to as a powerful immigrant figure in the land of Java. Although Habib's pre-sence is quite important in society, Habib's politics does not move or lose in the political constellation. This means that Habib's power is not always taken into account.